Temporal dynamics of zooplankton community in an oyster farming area of the Yellow Sea in China via metabarcoding - Qian, Beibei; Miao, Xiaojing; Xu, Fei (Frontiers in Marine Science, 2023)
Introduction The coastal ecosystem is a hub of both marine organisms and human activities. It plays a crucial role in human food production and affects facilities through biofouling. Long-read amplicon sequencing provides more accurate species identification and demonstrates numerous advantages in community diversity studies, making it an effective tool for ecological monitoring. Methods To investigate the zooplankton community characteristics in the oyster aquaculture area, the composition and temporal dynamics of zooplankton near Longwan Bay, Qingdao, China, were determined by the 18S rRNA gene long reads sequencing technique. Results A total of 89 zooplankton species were identified, among which copepods were the most abundant. Zooplankton composition and proportional abundances showed significant seasonal variations. The species richness in summer was the highest, while the species abundance in spring was the highest. Oyster farming showed weak influence on the zooplankton community variation. Paracalanus parvus abundance was higher in most assayed months. Chthamalus stellatus showed a strong temporal preference, with the highest percentage in May. Sea water temperature and species-species interactions were revealed to be the main contributors to the shifts in the community composition. Discussion The ubiquitous positive correlation between zooplankton suggests that species interactions are important in adaptation to the changing environment. The results reveal the seasonal occurrence of several major biofouling organisms and help improve biofouling management efficiency.